Production of bio‐based p‐xylene via catalytic pyrolysis of biomass over metal oxide‐modified HZSM‐5 zeolites. Issue 11 (6th June 2018) - Chang, Rui; Zhu, Lijuan; Jin, Feng; Fan, Minghui; Liu, Junxu; Jia, Qifang; Tang, Chi; Li, Quanxin
Abstract: BACKGROUND: p ‐Xylene is an important bulk chemical in the petrochemical industry, and the production of bio‐based p ‐xylene is of great significance in both academic and industrial arenas. However, the biggest challenge for the production of p ‐xylene from biomass is how to increase the yield and selectivity of p ‐xylene. RESULTS: The highest p ‐xylene yield of 20.7 C‐mol% with a p ‐xylene/xylenes ratio of 91.6% was obtained by the co‐catalytic pyrolysis of sawdust with 50 wt% methanol over the 20%La2 O3 /HZSM‐5(80) catalyst. Adding a La, Mg, Ce or Zn element into HZSM‐5 promoted the alkylation of benzene and toluene to form xylenes, and the isomerization of m/o ‐xylenes to p ‐xylene. CONCLUSION: This work developed a one‐pot process in which lignocellulosic biomass (sawdust) was directionally converted into p ‐xylene by coupling the catalytic pyrolysis of biomass into aromatic monomers, the alkylation of light aromatics to xylenes and the isomerization of m/o ‐xylenes to p ‐xylene over the metal oxide‐modified HZSM‐5 catalysts. The selectivity and yield of p ‐xylene strongly depended on the acidity of the catalysts, reaction temperature and methanol additive during the catalytic pyrolysis of sawdust. © 2018 Society of Chemical Industry